The Role of the ASEAN Socio-Cultural Community in Overcoming the COVID-19 Pandemic - A Indah Camelia; Koesrianti; Lina Hastuti (Yuridika, 2022)
The COVID-19 pandemic is described as circumstances often interchangeably in social and medical contexts as non-boundary spread and directly affected a wide range of human life and a non-traditional security threat. The pandemic has had adverse consequences on the economy, and health and psychology have suffered. In 2020, ASEAN  held an extraordinary summit on COVID-19 to accelerate resilience to the pandemic as a regional response; however, a solid commitment and comprehensive foundation are critical focal points for dealing with infectious diseases. Therefore, ASEAN member states should create a permanent mechanism to deal with current and future pandemics by providing a strategic long-term plan, an annual work plan, effective monitoring systems, and quality assurance by strengthening the ASEAN Socio-Cultural Community’s role as an open and dynamic entity within the ASEAN Community. Doctrinal research based on normative legal and conceptual approaches was conducted as methods for this study.